2016
DOI: 10.18632/oncotarget.11124
|View full text |Cite
|
Sign up to set email alerts
|

IL-2 augments the therapeutic efficacy of adoptively transferred B cells which directly kill tumor cells via the CXCR4/CXCL12 and perforin pathways

Abstract: We previously reported that antitumor B cells directly kill tumor cells via the Fas/FasL pathway and are regulated by IL-10. In this study, we defined additional mechanisms involved in B cell antitumor immunity. Administration of IL-2 significantly augmented the therapeutic efficacy of adoptively transferred tumor-draining lymph node (TDLN) B cells which express IL- 2R. Culture supernatant of purified B splenocytes harvested from the mice that received adoptive transfer of 4T1 TDLN B cells plus IL-2 administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 27 publications
2
33
0
Order By: Relevance
“…Yu et al demonstrated that transforming growth factor β (TGFβ) impairs MSCs ability to secrete CXCL12 and therefore promotes breast cancer metastasis [52], consistent with our findings. Recently, Xia et al found that B cells directly kill BC cells using CXCR4/CXCL12 pathways, indicating that CXCL12 functions as a tumor suppressor [53]. Bioinformatics analysis also suggested that CXCL12 is an independent prognostic indicator.…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al demonstrated that transforming growth factor β (TGFβ) impairs MSCs ability to secrete CXCL12 and therefore promotes breast cancer metastasis [52], consistent with our findings. Recently, Xia et al found that B cells directly kill BC cells using CXCR4/CXCL12 pathways, indicating that CXCL12 functions as a tumor suppressor [53]. Bioinformatics analysis also suggested that CXCL12 is an independent prognostic indicator.…”
Section: Discussionmentioning
confidence: 99%
“…The transfer also resulted in the induction of tumor-specific T-cell immunity as measured by cytotoxicity and the productions of cytokine interferon (IFN)-γ and granulocyte-macrophage colony-stimulating factor. In similar, TDLN B cells plus IL-2 administration ( 41 ) produced larger amounts of IgG, binding to 4T1, and led to cancer cells lysis. The study also suggested that TDLN B cells could kill cancer cells in CXCR4/CXCL12 pathways by cell-to-cell contact, which termed to be an additive manner.…”
Section: The Regulatory Mechanisms Of Til-b In Bcmentioning
confidence: 99%
“…2). B cells have also been reported to possess direct cytotoxic killing ability against murine 4TI breast cancer cells in a Fas/FasL-dependent manner in the absence of IL-10 107 and also in the presence of IL-2 108 …”
Section: B Cells In Melanoma Immune Surveillancementioning
confidence: 99%